The Italian Observatory on Food Surplus, Recovery, and Waste: The Development Process and Future Achievements - Grant, Federica; Rossi, Laura (Frontiers in Nutrition, 2022)
Food losses and waste (FLW) is an environmental, social, and economic problem. Countries around the world are looking for efficient strategies to prevent and reduce FLW, as recommended by the 12.3 Sustainable Development Goal (SDG) of the United Nations. The European Union (EU) is committed to contributing to help solve the FLW issue, setting up the Platform on Food Losses and Food Waste, and adopting the Farm to Fork strategy. Italy has a consolidated approach towards the redistribution of food surplus to those in need, which was instituted with the Gadda Law 166/2016. Under this normative framework, the National Observatory on Food Surplus, Recovery and Waste (OERSA) was established. The aim of this paper is to describe the creation and development of OERSA as the technical entity supporting national FLW policies. The first actions taken by OERSA were to map the FLW initiatives of the entire food supply chain. This enabled OERSA to establish two actionable directives: 1. collecting data regarding the primary production sector and at the consumer level; 2. establishing educational programs and awareness campaigns. The data collected by OERSA highlight that, although several actors of the Italian supply chain are already conscious of the causes of food losses and waste, new strategies that focus on innovation and cooperation should be encouraged.